Science : key concepts in philosophy - French, Steven (New York : Continuum, 2007)
An examination of the philosophy of science that covers key thinkers and their thoughts as well as central questions, problems, and arguments.
Discovery -- Heuristics -- Justification -- Observation -- Experiment -- Realism -- Anti-realism -- Independence -- Gender bias -- Appendix : where we've been and where to go for more.
Includes bibliographical references (p. 156-161) and index.
Adult
Keywords: Science -- Philosophy; Science -- Philosophy